Segmental stabilization and muscular strengthening in chronic low back pain: a comparative study - Fábio Renovato França; Thomaz Nogueira Burke; Erica Sato Hanada; Amélia Pasqual Marques (Clinics, 2010)
OBJECTIVE: To contrast the efficacy of two exercise programs, segmental stabilization and strengthening of abdominal and trunk muscles, on pain, functional disability, and activation of the transversus abdominis muscle (TrA), in individuals with chronic low back pain. DESIGN: Our sample consisted of 30 individuals, randomly assigned to one of two treatment groups: segmental stabilization, where exercises focused on the TrA and lumbar multifidus muscles, and superficial strengthening, where exercises focused on the rectus abdominis, abdominus obliquus internus, abdominus obliquus externus, and erector spinae. Groups were examined to discovere whether the exercises created contrasts regarding pain (visual analogical scale and McGill pain questionnaire), functional disability (Oswestry disability questionnaire), and TrA muscle activation capacity (Pressure Biofeedback Unit = PBU). The program lasted 6 weeks, and 30-minute sessions occurred twice a week. Analysis of variance was used for inter- and intra-group comparisons. The significance level was established at 5%. RESULTS: As compared to baseline, both treatments were effective in relieving pain and improving disability (p<0.001). Those in the segmental stabilization group had significant gains for all variables when compared to the ST group (p<0.001), including TrA activation, where relative gains were 48.3% and -5.1%, respectively. CONCLUSION: Both techniques lessened pain and reduced disability. Segmental stabilization is superior to superficial strengthening for all variables. Superficial strengthening does not improve TrA activation capacity.